Pengaruh Motivasi Internal dan Motivasi Eksternal Terhadap Kinerja Karyawan Divisi Sales CV. Sumber Baru Mandiri - Devita Sari; Siti Napisah; Ahmad Sulthoni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
High performance plays a pivotal role in achieving success and excellence across various domains of life, be it in business, education, sports, or even personal endeavors. One of the key factors that impacts performance is motivation at work. Motivation can be defined as the eagerness to exert maximum effort in order to attain organizational or company objectives. There exist two primary types of motivation, namely internal motivation and external motivation. The main goal of this study is to examine whether exists a relationship between internal motivation and external motivation concerning employee performance. The research was conducted with a sample population comprising 20 employees from the sales division. The research methodology employed was quantitative, utilizing a descriptive approach. Data analysis was executed through multiple linear regression analysis. Data gathering was accomplished through the administration of a questionnaire and observational techniques. The study's findings reveal that, in partial terms, internal motivation can exert a notable and favorable influence on employee productivity, whereas external motivation does not exhibit a discernible influence on employee performance. Additionally, the research identifies that both internal and external motivation can simultaneously affect employee performance.